Med majem '68 in novembrom '89 Transformacije sveta, literature in teorije - Juvan, Marko (Studia litteraria, 2021)
The authors of the volume ('From May '68 to November '89: Transformations of the World, Literature, and Theory') intervene in the study of the student movement's "rehearsal" for a world revolution and its afterlife in the 1980s and 1990s by addressing two hitherto neglected aspects - the literary and the peripheral. They consider the roles played by the (semi-)periphery of the modern world-system, on the one hand, and modernist literature and theory, on the other, in transforming the existing world order in the fields of culture, politics, economy, and everyday life. How were critical theory and neo-avant-garde literature in the world, in Slovenia, and in Yugoslavia intertwined with the student protest that advocated the transformation of the capitalist world-system and its socialist counterpart? The monograph focuses on the processes that connected the events of 1968 and 1989 in the social, literary, and theoretical spheres in the sign of continuity and turning points, and at the same time defined our contemporary world.